PD-L1 Expression in Glioblastoma, the Clinical and Prognostic Significance: A Systematic Literature Review and Meta-Analysis - Hao, Chengcheng; Chen, Gang; Zhao, Huishan; Li, Yan; Chen, Jianxin; Zhang, Hongmei; Li, Shan; Zhao, Yuze; Chen, Feng; Li, Wenbin; Jiang, Wen G. (Frontiers in Oncology, 2020)
Background: The clinical and prognostic value of programmed death-ligand 1, PD-L1, in glioblastoma remains controversial. The present study aimed to identify the expression of PD-L1 for its prognostic value in glioblastoma. Methods: A comprehensive literature search was performed using the PubMed and CNKI databases. The overall survival (OS) and disease-free survival (DFS) of GBM was analyzed based on Hazard ratios (HRs) and 95% confidence intervals (CIs). Furthermore, Odds ratios (ORs) and 95% CIs were summarized for clinicopathological parameters. The statistical analysis was using RevMan 5.3 software. Results: The meta-analysis was performed by using total nine studies including 806 patients who had glioblastoma. The pooled results indicated that PD-L1 expression in tumor tissues was significantly related to a poor OS (HR = 1.63, 95%CI: 1.19–2.24, P = 0.003, random effects model) with heterogeneity (I2 = 51%). In subgroup analyses, PD-L1 positivity was significantly associated with a worse OS for patients of American and Asian regions, but not for those of European regions. Moreover, PD-L1 expression implied a trend toward the mutation status of the IDH1 gene [coding the Isocitrate Dehydrogenase (NADP(+))-1 protein] (HR = 9.92, 95%CI: 1.85–53.08, P = 0.007, fixed effects model). However, the prediction overall survival (OS) of the patients showed that PD-L1 expression was independent from other clinicopathological features, such as gender and age. Conclusions: Our analyses indicated that high expression of PD-L1 in glioblastoma tumor tissues is associated with poor survival of patients, and PD-L1 may act as a prognostic predictor and an effective therapeutic target for glioblastoma.